Influence of grapevine (Vitis vinifera L.) on cover crops: a biomathematical model of the transition of amensalism to comensalism - Bageta, Carlos Rubén; Alberto, Marcelo; Sartor, Carmen; Cecconato, Adrián; Bevaqua, Alicia; Tirador, Marta; Garriga, Marcela; Nodaro, Verónica; Quiroga, Alejandro; Uliarte, Ernesto (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2018)
In this paper, we study the dynamics of transition in the interaction between vine (Vitis vinifera L.) and cover crop. From data obtained in a field essay, we propose a statistical model to investigate such biological interaction and we could determine that the vine-cover crop system changed from a biological interaction of commensalism type to another of amensalism type, being the vine not affected. Based on this information, we formulate a biomathematical model to describe this interaction, we estimate its parameters, and analyze the stability of the equilibrium points. It is evident, in this study, that the cover crop does not affect vine growth during the period considered in the essay.